2014
DOI: 10.1364/oe.22.031801
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optical dual-cantilever arrays in silica on silicon

Abstract: A dual cantilever device has been demonstrated which can operate as a force sensor or variable attenuator. The device is fabricated using physical micromachining techniques that do not require cleanroom class facilities. The response of the device to mechanical actuation is measured, and shown to be well described by conventional fiber optic angular misalignment theory. The device has the potential to be utilized within integrated optical components for sensors or attenuators. An array of devices was fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The problem of mechanical structures breaking is mentioned, as well as a solution: anti-buckling structures in combination with a specific Si etching process. Cooper et al [ 8 ] demonstrated suspended silica waveguides with a cross-section of 100 × 40 . Their waveguide material is thermal SiO in combination with silica created by flame hydrolysis deposition (FHD), and the suspended waveguides are realized by a combination of dicing and wet etching.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of mechanical structures breaking is mentioned, as well as a solution: anti-buckling structures in combination with a specific Si etching process. Cooper et al [ 8 ] demonstrated suspended silica waveguides with a cross-section of 100 × 40 . Their waveguide material is thermal SiO in combination with silica created by flame hydrolysis deposition (FHD), and the suspended waveguides are realized by a combination of dicing and wet etching.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] [3]. In this invited paper work conducted at Southampton University will be presented, making use of novel fabrication techniques for producing arrays of cantilevers incorporating optical waveguides [4].…”
Section: Introductionmentioning
confidence: 99%